The price of broadband quality: tracking the changing valuation of service characteristics - Bryan Coynea; Sean Lyonsa (International Telecommunications Society (ITS), 2015)
This paper investigates how retail broadband prices, choice and quality are changing over time. Using a dataset containing daily observations of plans offered in Ireland from 2007 to 2013, this paper applies hedonic modelling techniques to observe the changing pricing of service characteristics. We augment our results by restricting the analysis to large operators and also by weighting by operator market share for a subset of our data (2010-2013). Although we find that average nominal prices remain static throughout our sample period, quality of service has risen dramatically over time, particularly with respect to download speed. Some characteristics of broadband plans exhibit broadly stable valuations over time, but the elasticity of price with respect to advertised download speed and the premium on bundled plans declined during the sample period. In addition, the retail price premium enjoyed by the incumbent operator fell significantly since 2007.
Keywords: L11; L96; 330; broadband services; market analysis; Ireland